Pulmonary arterial hypertension in pregnancy—a systematic review of outcomes in the modern era - Ting-Ting Low (Pulmonary Circulation, 2021)
Pregnancy is hazardous with pulmonary arterial hypertension, but maternal mortality may have fallen in recent years. We sought to systematically evaluate pulmonary arterial hypertension and pregnancy-related outcomes in the last decade. We searched for articles describing outcomes in pregnancy cohorts published between 2008 and 2018. A total of 3658 titles were screened and 13 studies included for analysis. Pooled incidences and percentages of maternal and perinatal outcomes were calculated. Results showed that out of 272 pregnancies, 214 pregnancies advanced beyond 20 gestational weeks. The mean maternal age was 28 ± 2 years, mean pulmonary artery systolic pressure on echocardiogram was 76 ± 19 mmHg. Etiologies include idiopathic pulmonary arterial hypertension (22%), congenital heart disease (64%), and others (15%). Majority (74%) had good functional class I/II. Only 48% of women received pulmonary arterial hypertension-specific therapy. Premature deliveries occur in 58% of pregnancies at mean of 34 ± 1 weeks, most (76%) had Cesarean section. Maternal mortality rate was 12% overall ( n  = 26); even higher for idiopathic pulmonary arterial hypertension etiology alone (20%). Reported causes of death included right heart failure, cardiac arrest, pulmonary arterial hypertension crises, pre-eclampsia, and sepsis; 61% of maternal deaths occur at 0–4 days postpartum. Stillbirth rate was 3% and neonatal mortality rate was 1%. In conclusion, pulmonary arterial hypertension in pregnancy continues to be perilous with high maternal mortality rate. Continued prospective studies are needed.